Perilaku orang tua dalam pemberian makan dan status gizi anak usia 2-5 tahun - Ni Luh Agustini Purnama; Lely Lusmilasari; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2015)
Background: The issue of child nutrition is still a problem in developing countries, including Indonesia. Nowadays, there is double burden related to child nutrition, due to lack of nutrition that has not been resolved and at the same time, there is an increasing problem of excess nutrients. Parents are responsible for the care of children, including fulfilling a balanced nutritional intake.Objective: To identify the relationship between parent’s behavior in feeding and nutritional status of children aged 2-5 years.Method: Design used in this study was observational with the cross-sectional study was conducted 153 parents with children aged 2-5 years who fit the inclusion and exclusion criteria in the region of Integrated Health Center Catholic Hospital St. Vincentius a Paulo Surabaya. Parent’s behavior in feeding was assessed using the Comprehensive Feeding Practices Questionnaire (CFPQ) which consists of 49 questions and 12 behavioral aspects. The nutritional status of children assessed by weight indicator according to height (weight/height) were compared with z-score WHO 2006 standard. Data were analyzed using the Spearman correlation.Results: The average nutritional status of children aged 2-5 years based on the weight/height z-score indicator was 0.17 indicating that is in normal condition. Parent’s behavior that involves children in the planning and preparation of meals, positively associated with nutritional status of children in all conditions of nutritional status of children who are very thin to obese (ρ=0.43; p=0.001). Pressure, when children eat, was negatively associated with nutritional status of children aged 2-5 years in normal nutritional status to obese (ρ=-0.34; p=0.001). Restriction of food intake to control body weight was positively associated with nutritional status of children aged 2-5 years in all conditions of nutritional status of children who are very thin to obese (ρ=0.29; p=0.001).Conclusion: Parent’s behavior in feeding the children associated with nutritional status of children aged 2-5 years.